Prevalence of larvae of the bot fly Cuterebra simulans (Diptera, Oestridae) on Gracilinanus microtarsus (Didelphimorphia, Didelphidae) in southeastern Cerrado from Brazil - Cruz, Leonardo Dominici [UNESP]; Fernandes, Fernanda Rodrigues [UNESP]; Linhares, Arício Xavier (Sociedade Brasileira de Entomologia, 2009)
A prevalência de parasitismo das larvas da mosca Cuterebra simulans no marsupial Gracilinanus microtarsus foi comparada entre os sexos e estações do ano. Machos e fêmeas não apresentaram diferenças significativas, mas a prevalência de parasitismo foi mais elevada na estação quenteúmida que na estação fria-seca. Este padrão está de acordo com as observações de outros estudos com moscas da família Oestridae realizados nas áreas ao sul da região Neotropical, sugerindo a ocorrência de mudanças latitudinais nos picos de atividades reprodutivas destas moscas em relação às estações do ano ao longo destes sistemas. Este também é o primeiro registro da ocorrência de C. simulans em áreas mais ao sul da região Neotropical e do parasitismo de suas larvas em G. microtarsus.

The prevalence of Cuterebra simulans bot fly parasitism on marsupial Gracilinanus microtarsus was compared between sexes and seasons of the year. No significant difference was observed between females and males but prevalence was higher in warm-wet season than cool-dry season. This pattern agree with observations of others studies with oestrids flies in southern Neotropical areas, suggesting the occurrence of latitudinal change in the peak of bot flies reproductive activity related to seasons of the year along these systems. This is the first record of C. simulans larvae parasitism on G. microtarsus and its occurrence in southern areas of the Neotropical region.
Prevalência de parasitismo de larvas de Cuterebra simulans (Diptera, Oestridae) em Gracilinanus microtarsus (Didelphimorphia, Didelphidae) no Cerrado do sudeste do Brasil
Keywords: Miíase; marsupial; parasitismo; mosca do berne; Bot fly; myiasis; opossum; parasitism